Dampak Rotasi Wilayah terhadap Motivasi Kerja Karyawan di Kebun Karang Agung Estate - Muhamad Fazrul Hizri Alfani; Tri Endar Suswatiningsih; Siwi Istiana Dinarti (Program Studi Agribisnis INSTIPER Yogyakarta, 2023)
Employee performance is an important part of a company engaged in oil palm plantations. One of the company's regional rotation policies aims to improve employee performance. The aims of this study were to determine (1) the work area rotation system in Karang Agung Estate, Lencir, South Sumatra, (2) employee motivation at Karang Agung Estate, Lencir, South Sumatra, (3) the impact of area rotation on employee motivation in Karang Agung Estate, Lencir, South Sumatra. The basic research method used in this research is descriptive method with a quantitative approach, with 28 respondents. The data were analyzed using Chi Square. The results of this study indicate that the area rotation system in Karang Agung Estate consists of a regional rotation system for staff employees and a regional rotation system for non-staff employees. The average employee motivation is in the medium category. There is no significant impact of work area rotation on employee motivation.